Zirconium Oxychloride as a Novel Mordant for Natural Dyeing of Wool Yarns. (20th February 2013) - Forouharshad, M.; Montazer, M.; Yadollah Roudbari, B.
Abstract : Zirconium oxychloride, a well-known flame retardant, is introduced as a novel mordant for wool dyeing. This has been indicated by mordanting of wool yarns with zirconium oxychloride in different conditions and then dyeing with madder as a famous natural dye. The tenacity, color coordinates, washing, and light fastnesses of the dyed wool confirmed the positive influence of zirconium oxychloride as a useful mordant for wool dyeing with a low impact on the color coordinates. Further, an appropriate washing and light fastness were obtained for the zirconium-oxychloride-mordanted wool yarns. The central composite design (CCD) was used to design the experiments with four variables on the results of tensile strength. Statistical analysis confirmed the optimum conditions obtained through the experimental results.